Pengaruh Corporate Governance Terhadap Firm Value Dengan Financial Performance Sebagai Variabel Intervening Pada Perusahaan LQ 45 Tahun 2012-2015 - Natasha Irawan; Devie Deviesa (Business Accounting Review, 2017)
The purposes of this research was to analyze  the relationship of corporate governance to firm value with financial performance as intervening variable. The data analysis technique used was Partial Least Square (PLS)  with the calculation process assisted by SmartPLS software application program to process the data from the Annual report. The results showed there were positive and significant influence of corporate governance towards firm value and financial performance, positive and siginificant of financial performance towards firm value. There was no indirect influence of corporate governance towards firm value through financial performance.